2021
DOI: 10.1093/ofid/ofab149
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of SARS-CoV-2 in Household Members and Other Close Contacts of COVID-19 Cases: A Serologic Study in Canton of Vaud, Switzerland

Abstract: Background Research on SARS-CoV-2 transmission within households and other close settings using serological testing is scarce. Methods We invited COVID-19 cases diagnosed between February 27 and April 1, 2020, in canton of Vaud, Switzerland, to participate, along with household members and other close contacts. Anti-SARS-CoV-2 IgG antibodies were measured using a Luminex immunoassay. We estimated factors associated with serol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…The findings complement qualitatively the quantitative results of the SérocoViD project by shedding light on the reconfigurations of care and gender in the daily navigation of risk and protection, which was not captured by the quantitative approach. They confirm the epidemiological importance of the household (Dupraz et al, 2020) as a key determinant in understanding how families managed viral transmission and protection. But what are the consequences of these observations for the management of the pandemic at national level?…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The findings complement qualitatively the quantitative results of the SérocoViD project by shedding light on the reconfigurations of care and gender in the daily navigation of risk and protection, which was not captured by the quantitative approach. They confirm the epidemiological importance of the household (Dupraz et al, 2020) as a key determinant in understanding how families managed viral transmission and protection. But what are the consequences of these observations for the management of the pandemic at national level?…”
Section: Discussionsupporting
confidence: 60%
“…As epidemiological studies have shown, the domestic space is a privileged site for transmission (Dupraz et al, 2020), putting extra pressure on family members to negotiate risk in their daily lives, especially when several generations share the same space. The literature in early 2020 did not show clearly how care activities, borne mainly by women, and more broadly gender and intergenerational dynamics, affected and intersected with viral exposure and protective measures.…”
Section: Introductionmentioning
confidence: 99%
“…For fever (Fig. 1 ), 16/18 studies reported higher frequency for index cases than secondary cases 15 17 , 19 23 , 26 , 27 , 29 , 31 , 38 , 40 , 41 , 48 , with 11 of them reported significant difference 15 , 17 , 19 , 21 23 , 26 , 29 , 38 , 41 , 48 . For cough (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…On the basis of our selection criteria, 561 of those studies were excluded and 38 met our inclusion criteria 15 52 (Table S1 ). Of these, 19 studies provided information on types of symptoms 15 23 , 26 – 29 , 31 , 38 , 40 , 41 , 44 , 48 , 10 studies provided information on case severity 15 , 18 , 23 , 24 , 26 , 29 , 30 , 32 , 35 , 44 , 33 studies provided symptom status 15 , 16 , 18 , 19 , 21 – 26 , 28 30 , 32 , 34 42 , 44 , 46 – 52 , 10 studies provided hospitalization 30 , 33 , 34 , 36 , 37 , 39 , 43 , 48 , 50 , 51 , and 7 studies provided fatality 27 , 30 , 33 , 37 , 39 , 43 , 45 for both index and secondary cases. Overall, 50,382 index cases and 30,309 secondary cases provided information on at least one measure of clinical severity and type of symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation